Exploring psychology - Myers, David G.; DeWall, C. Nathan (New York : Worth Publishers, 2021)
"Introductory psychology textbook. Psychological science insights enable students to be more successful in their courses, more tuned-in as friends and partners, more effective as co-workers, and wiser as parents. And helping students to think more like psychological scientists will arm them with the critical-thinking skills they need to think smart and challenge misinformation in our post-truth world"--
ESS
Book Finder International
Keywords: Psychology